Measuring social capital change using ripple mapping1. Issue 138 (22nd July 2013) - Baker, Barbara; Johannes, Elaine M.
Abstract: This article provides a detailed description of how to implement a ripple mapping activity to assess youth program effects on community capital and concludes with examples from Maine and Kansas. The maps lead to group reflection on project outcomes and further research and evaluation questions for group members. The results from five Maine communities showed that youth in schools and community clubs promoted intentional, mutually beneficial relationships with community groups and businesses and increased shared action on community projects. Likewise, youth in five small Kansas towns implemented and evaluated health promotion projects and found through mapping that youth built social capital in addition to awareness, knowledge, and skills in community health promotion. Ripple mapping helped to demonstrate that actions of youth‐adult partnerships in both states improved the built, human, and social capital in small towns.